Cell cycle parameters of Escherichia coli K-12. - Allman, R (1991)
A computer simulation routine was used to calculate the DNA distributions of exponentially growing cultures of Escherichia coli K-12. Simulated distributions were compared with distributions obtained experimentally by flow cytometry. Durations of the DNA replication period (C) and the postreplication period (D) were found by minimizing the difference between theoretical and experimental DNA histograms. It was demonstrated that the K-12 strains AB1157 and CM735 had C and D periods that differed widely from each other and from those of the previously measured strain B/rA, while strain MC1000 was shown to have the same durations of the C and D periods as strain B/rA. The variation between K-12 strains may explain the divergence in the literature regarding their C and D periods. Strains W3110 and AB1157 recA1 had DNA histograms that could not be adequately simulated by the classical Cooper-Helmstetter model, which is consistent with the asymmetrically located origin and terminus for W3110 and the asynchrony of initiation for AB1157 recA1.